(untitled) (Journal of Engineering, 2006)
In most of the construction projects, there are many events or risks may occur during the execution of project. These risks (e.g. the excess of project cost or the expected time, increasing the prices of material and labor, accidents, changes, engineering errors or omissions, bad quality, delay in reaching the facilities to the site, etc.) may effect negatively on the project and the parties. Therefore, these risks must be identified and assessed accurately to avoid or reduce the negative effects for these risks. The concept of risk is used to assess and evaluate uncertainties associated with an event or a process. A construction process includes many uncertainties, therefore, the construction project’s parties are becoming aware of the construction process and thus the risks within this process are seeking more and more clarification that all is being done to remove foreseeable risk and minimize unforeseeable risk. It is also becoming clear that generic approaches to the management of risk are maturing and becoming easier to apply.